Inspiration Through Advertising Pop-Up in Batam Communities and Consumers - Tan, Jefry; Anggriani, Diny (Journal of Research and Investigation in Education, 2025)
The rapid increase in the use of Information and Communication Technology (ICT) in society has affected significant changes in entertainment media specifically in the field of video games. Ads in video games can affect user behavior, especially in the Inspired-To. Therefore, to understand more about Inspired-To that can affect the behavior of video game users, the writer will carry out this research using a questionnaire (N=390) and interviews (N=30) among video game users. In this study the authors found that the users were satisfied with the results of the advertisements pop up if the content is entertaining and provides benefits in the form of incentive. The author also identifies that each of the advertisements pop up entertaining and providing incentive benefits can increase the value of the ad. The writer finds that a good ad value can trigger a state of being inspired to the users in discovering something new which will then be followed by a state of being inspired to download the new game offered by the ad pop up. This study will assist users in identifying factors that can increase the state of being inspired in downloading a new game.The rapid increase in the use of Information and Communication Technology (ICT) in society has affected significant changes in entertainment media specifically in the field of video games. Ads in video games can affect user behavior, especially in the Inspired-To. Therefore, to understand more about Inspired-To that can affect the behavior of video game users, the writer will carry out this research using a questionnaire (N=390) and interviews (N=30) among video game users. In this study the authors found that the users were satisfied with the results of the advertisements pop up if the content is entertaining and provides benefits in the form of incentive. The author also identifies that each of the advertisements pop up entertaining and providing incentive benefits can increase the value of the ad. The writer finds that a good ad value can trigger a state of being inspired to the users in discovering something new which will then be followed by a state of being inspired to download the new game offered by the ad pop up. This study will assist users in identifying factors that can increase the state of being inspired in downloading a new game.